2009
DOI: 10.4103/1319-3767.48967
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin-E on rat liver-amiodarone: An ultrastructural study

Abstract: Background/Aim:Amiodarone, a class III antiarrhythmic drug, has been found to be effective in the management of patients with life-threatening ventricular arrhythmias. The aim of this study was to test whether the co administration of vitamin-E with amiodarone can reduce amiodarone-induced liver damage.Materials and Methods:Twelve male albino rats were divided into three groups (ml vegetable oil/day by oral gavages daily for 2 weeks and were used as control group. The rats of the second group received 5.4 mg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…Because vitamin E is the most potent protectant against AMD-induced liver injury in rats (Agoston et al, 2003), it was applied as a positive control in our investigation, which dramatically suppressed GSH depletion and lipid peroxidation (LPO), but showed little effect on lipid accumulation induced by AMD (Figure 2). The detected GSH retrieval and lipid reduction by vitamin E were all well in agreement with its antioxidant effects in vivo (Agoston et al, 2003;Zaki & Eid, 2009).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Because vitamin E is the most potent protectant against AMD-induced liver injury in rats (Agoston et al, 2003), it was applied as a positive control in our investigation, which dramatically suppressed GSH depletion and lipid peroxidation (LPO), but showed little effect on lipid accumulation induced by AMD (Figure 2). The detected GSH retrieval and lipid reduction by vitamin E were all well in agreement with its antioxidant effects in vivo (Agoston et al, 2003;Zaki & Eid, 2009).…”
Section: Discussionsupporting
confidence: 78%
“…So far, only vitamin E, a lipophilic antioxidant, was proposed to potently attenuate AMD-induced toxicity in vivo (Agoston et al, 2003;Zaki & Eid, 2009) or in cultured hepatocytes (Ouazzani-Chahdi et al, 2007;Ruch et al, 1991). Such protection could be further enhanced by synergistic use of ursodeoxycholic acid or its nitric-oxidereleasing derivative, NCX-1000 (Ouazzani-Chahdi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These findings were in agreement with Yu et al, (2011) who found that vitamin E may increase thyroid antioxidant defenses and inhibit iodine-induced thyroid cytotoxicity [37] . Also, Zaki, and Eid, (2009) who observed that α tocopherol could protect rat hepatocytes in culture from the damaging effect of amiodarone [20] . Murray et al (2000) reported that vitamin E protects against peroxidation of polyunsaturated fatty acids, which were part of cellular and subcellular membrane phospholipids [38] .…”
Section: Discussionmentioning
confidence: 98%
“…Cappiello et al (1995) suggested that amiodarone increases the permeability of the mitochondrial membrane with subsequent diffusion of glycogen synthesis enzymes that increase the intramitochondrial glycogen [36] . Also, Zaky and Eid, (2018) clarified that intramitochondrial accumulation of lipid droplets occurred due to inhibition of mitochondrial beta-oxidation by amiodarone therapy [20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation